2015
DOI: 10.1128/aac.03949-14
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with Teicoplanin and Cefuroxime Reduces the Rate of Prosthetic Joint Infection after Primary Arthroplasty

Abstract: The aim of this study was to compare the prosthetic joint infection (PJI) rate after total joint arthroplasty in two consecutive periods of treatment with different antibiotic prophylaxes: cefuroxime versus cefuroxime plus teicoplanin. We retrospectively reviewed 1,896 patients who underwent total hip arthroplasty or total knee arthroplasty between March 2010 and February 2013. From March 2010 to August 2011, patients received 1.5 g of cefuroxime during induction of anesthesia and another 1.5 g 2 h later (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 31 publications
2
20
1
Order By: Relevance
“…Resistant Gram-positive organisms are the most common cause of SSIs following joint replacement surgery in Australia and are associated with poorer outcomes 14 22–24. These resistant Gram-positive organisms, including methicillin-resistant Staphylococcus aureus (MRSA), other methicillin-resistant Staphylococcus species and Enterococcus species, cause over 50% of all culture-positive infections in Australia, which is similar to international reports 22 25–33…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Resistant Gram-positive organisms are the most common cause of SSIs following joint replacement surgery in Australia and are associated with poorer outcomes 14 22–24. These resistant Gram-positive organisms, including methicillin-resistant Staphylococcus aureus (MRSA), other methicillin-resistant Staphylococcus species and Enterococcus species, cause over 50% of all culture-positive infections in Australia, which is similar to international reports 22 25–33…”
Section: Introductionsupporting
confidence: 57%
“…In particular, large cohort studies by Sewick et al and Liu et al reported a reduction in the incidence of SSIs isolating resistant Gram-positive organisms following adoption of combination prophylaxis with vancomycin and cefazolin 48 50. Similarly, Tornero et al reported a 64% reduction in the overall rate of prosthetic joint infection following the adoption combination prophylaxis with teicoplanin and cefuroxime (1.26% vs 3.51%; p=0.002); of note, there was a significant reduction in all Staphylococcus aureus SSIs (methicillin resistant and sensitive) in the combination prophylaxis cohort (0 vs 21 SSIs; p=0.0001) 30. This suggests a potential synergy between glycopeptides and beta-lactams, which is corroborated by other laboratory and clinical studies 51 52.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, a study with before-and-after design compared 995 patients who received only cefuroxime with 791 who received cefuroxime and teicoplanin (another antibiotic from glycopeptide group) as surgery prophylaxis. They showed that the PJI rate in the group with teicoplanin addition was lower than in the cefuroxime only group (1.3% versus 3.5%) [11]. This study did not mention delayed PJI specifically due to coagulase-negative staphylococci.…”
Section: Vancomycin For Surgical Prophylaxismentioning
confidence: 57%
“…Decisions on using single versus dual‐agent prophylaxis should depend on local epidemiology, and resistant rates addressing particular needs . Similarly, glycopeptide prophylaxis has led to a significant relative risk reduction for SSI from MRSA . However, combining antibiotics such as vancomycin and cefazolin comes with higher risks of acute kidney injury.…”
Section: Resultsmentioning
confidence: 99%